147Sm‐143Nd and 176Lu‐176Hf systematics of eucrite and angrite meteorites. (16th October 2015) - Bouvier, Audrey; Blichert‐Toft, Janne; Boyet, Maud; Albarède, Francis
Abstract: Comparative planetary geochemistry provides insight into the origin and evolutionary paths of planetary bodies in the inner solar system. The eucrite and angrite achondrite groups are particularly interesting because they show evidence of early planetary differentiation. We present 147 Sm‐ 143 Nd and 176 Lu‐ 176 Hf analyses of eight noncumulate (basaltic) eucrites, two cumulate eucrites, and three angrites, which together place new constraints on the evolution and differentiation histories of the crusts of the eucrite and angrite parent bodies and their mantle mineralogies. The chemical compositions of both eucrites and angrites indicate similar evolutionary paths and petrogenetic models with formation and isolation of differentiated crustal reservoirs associated with segregation of ilmenite. We report a 147 Sm‐ 143 Nd mineral isochron age for the Moama cumulate eucrite of 4519 ± 34 Ma (MSWD = 1.3). This age indicates protracted magmatism within deep crustal layers of the eucrite parent body lasting up to about 50 Ma after the formation of the solar system. We further demonstrate that the isotopic compositions of constituent minerals are compromised by secondary processes hindering precise determination of mineral isochron ages of basaltic eucrites and angrites. We interpret the changes in geochemistry and, consequently, the erroneous 147 Sm‐ 143 Nd and 176 Lu‐ 176 Hf internal mineral isochron ages of basaltic eucrites and angrites as the result of metamorphic events such as impacts (effects from pressure, temperature, and peak shock duration) on the surfaces of the eucrite and angrite parent bodies.